View of West Fourth Street looking west at North Main Street, 1918. - Russell & Moses Studio (Forsyth County Public Library, 1918)
Source: Booklet, "City of Industry," 1918.
View of West Fourth Street looking west at North Main Street, 1918. The 100 block of West Fourth Street is at right, with the Kress Store in the center of the block.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources